Waves of Waste The Textile Industry's Contribution to Ocean Pollution - Muhammad Naeem; Muhammad Waheed (RADINKA JAYA UTAMA PUBLISHER, 2023)
The world's most polluting industry is the textile industry. in order for such industries to harm the ecology as well. Industries have an impact on biomes, which limits how well plants and animals can breathe. Apart from that, the water discharged by the textile factories contributes to water contamination. Dust, which causes respiratory issues, also affects the workers. The staff are required to adhere to the standard operating procedures (SOP). To reduce the impact of the hazards, management should enforce safety standards. By doing this, the environmental pollutants will be removed. Wastewater should be treated using cleaner technology that promotes long-term development in our environment so that the ecosystem may exist without having an impact on the conditions of the environment. This will preserve water for the environment's future. The textile industry need to maintain a focus on worker safety and waste management.